Effects of Solar Radiation on the Cyanobacteria: Diversity, Molecular Phylogeny, and Metabolic Activity - Wang, Zhikai; Li, Guo; Huang, Haiqing; Zhang, Weizhen; Wang, Jie; Huang, Suzhen; Zheng, Zheng (Frontiers in Ecology and Evolution, 2022)
Cyanobacteria bloom is a global aquatic ecological problem that seriously threatens human health and social development. The outbreak of cyanobacteria bloom is affected by various environmental factors, among which light intensity is an essential factor inducing cyanobacteria bloom. In this study, the growth changes of cyanobacteria under different amounts of natural light were studied by simulating different depths of Taihu Lake, and we used 16S rRNA and non-targeted metabolomics for sequencing to reveal the effects of light on the diversity of cyanobacteria and coexisting microorganisms, and to analyze the changes of related genes, functional structures and internal metabolism involved in nitrogen cycling. The result shows that excessive and insufficient light could inhibit the growth, photosynthesis, and EPS secretion of cyanobacteria, resulting in an antioxidant stress response. At the same time, the amount of natural light affects the vertical distribution of cyanobacteria, and under the condition of 1/3 natural light, cyanobacteria first appeared to float. In addition, the amount of natural light affects the diversity, abundance, and metabolites of cyanobacteria and coexisting microorganisms, and the expression of nifH, nirK, and nirS, three nitrogen-fixing genes, is significantly different in different genera. This study provides valuable information on the molecular mechanism of the effects of the amount of natural light on cyanobacteria bloom.